Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-92003-7
|View full text |Cite
|
Sign up to set email alerts
|

Phrenic nerve block during nonintubated video-assisted thoracoscopic surgery: a single-centre, double-blind, randomized controlled trial

Abstract: There has been interest in the use of nonintubated techniques for video-assisted thoracoscopic surgery (VATS) in both awake and sedated patients. The authors’ centre developed a nonintubated technique with spontaneous ventilation for use in a patient under general anaesthesia using a phrenic nerve block. This treatment was compared with a case-matched control group. The authors believe that this technique is beneficial for optimizing anaesthesia for patients undergoing VATS. The patients were randomly allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Vagal blockade should be considered in cases in which more complex lung resections involving hilar dissection are planned 14,15 . In addition, Zhu et al 16 concluded that phrenic nerve blockade may reduce anesthetic doses, provide faster recovery, and result in fewer additional complications during N-VATS. Ipsilateral stellate ganglion blockade, lidocaine infusion, or lidocaine inhalation 30 min before surgery can also be used to reduce the coughing reflex 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Vagal blockade should be considered in cases in which more complex lung resections involving hilar dissection are planned 14,15 . In addition, Zhu et al 16 concluded that phrenic nerve blockade may reduce anesthetic doses, provide faster recovery, and result in fewer additional complications during N-VATS. Ipsilateral stellate ganglion blockade, lidocaine infusion, or lidocaine inhalation 30 min before surgery can also be used to reduce the coughing reflex 17 .…”
Section: Discussionmentioning
confidence: 99%
“…But the complication rate remains 41%-48%, with major complication (Clavien-Dindo classification ≥ III) ranged from 10%-12% (4), revealing that to shorten the recovery time after esophagectomy and reduce the incidence of postoperative complication still challenge the anesthetist and surgeons. Nonintubated video-assisted thoracoscopic surgery recently has been demonstrated to be a safe and feasible approach for various thoracic diseases (5,6), but the application of this procedure in esophageal surgery has not been well depicted.…”
Section: Introductionmentioning
confidence: 99%